Long-Term Outcomes and Recurrence Rates After Microvascular Decompression in Trigeminal Neuralgia: A Tertiary Care Experience with 45 Patients - Muhammad Irshad, Shakeel Ahmed, Ali Manzoor, Atta Ur Rehman, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Microvascular decompression (MVD) is a well-established surgical treatment for trigeminal neuralgia (TGN), offering significant long-term pain relief. Objective: To evaluate the long-term outcomes and recurrence rates following MVD in a cohort of 45 TGN patients at our institute. Methods: A retrospective analysis was conducted on 45 patients who underwent MVD for TGN between 2017 and 2019. Data on demographics, clinical presentation, surgical details, and follow-up outcomes were collected and analyzed. Results: Immediate postoperative pain relief was achieved in 92% of patients. At a mean follow-up of 5 years, 85% of patients remained pain-free, while 8.9% experienced partial recurrence, and 4.4% had complete recurrence. Conclusion: MVD remains a highly effective treatment for TGN, with sustained long-term pain relief in the majority of patients. Keywords: Trigeminal neuralgia, microvascular decompression, recurrence rates, long-term outcomes.